Improvement of Gasoline Octane Number by Using Organic Compounds - Baghdad Science Journal (مجلة بغداد للعلوم, 2014)
The toxic lead additives to gasoline are no longer used in many countries around the world. Many other countries are now phasing out the lead in gasoline. Although the lead fuel is still in use in Iraq, several plans are considered to phase out the lead. The use of organic compounds to replace the lead additives in gasoline is considered now as an option in Iraqi refineries. The main objective of this project was preparation of premium gasoline, by blending of gasoline with Alternative additives (alcohol, aromatic) to enhancing octane number of Al-Doura gasoline pool. Improved gasoline was tested by ASTM standard method which includes octane number measuring by CFR engine analyzer. Gasoline pool RON (80) was used and selective components were added to the gasoline pool (1-3%) to improving it octane, such as ethanol, methanol,isopropanol,isobutanol, benzene, nitrobenzene, Aniline, and nitro aniline. Octane number of blends was measured by CFR engine. Mixture of alternative additives was prepared and adding in 1-3%vol to the gasoline pool. It was found that the additives show significant improvement of octane number of gasoline but the important increasing of RON was shown on use mixture of alcohols and aniline.